PELAYANAN PT. PLN (PERSERO) PADA KONSUMEN PRABAYAR RAYON PANAM KOTA PEKANBARU - Betty Cahyani; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Services of PT. PLN (Limited Liability Company) In Prepaid Consumers Rayon Panam City Pekanbaru has been running since 2009. This research was conducted to obtain and view information about the community in receiving services from PT. Prepaid PLN for consumers. The launch of the prepaid electricity program is a manifestation of PLN's commitment to continuously improve its services to customers with various forms of innovation. The concept of service is not the same, depending on the perceptions of each person who receives the service. Therefore, it is very important for PT PLN (Limited Liability Company) Rayon Panam to find out how much the quality of service for Prepaid consumers they provide to customers and to find out what factors influence the operation of PT. PLN (Limited Liability Company) on consumers prepaid Rayon Panam Pekanbaru City. The theoretical concept used in this study is the service theory in the Budiman book, namely: (1) Reliability, (2) Tangibles (direct evidence), (3) Responsiveness (responsiveness), (4) Assurance (guarantee), (5) Empathy (empathy). This research uses descriptive qualitative method with descriptive data analysis. In data collection researchers used observation, interview and documentation techniques. Based on the results of the study through interviews and observations, it can be seen that the services of PT. PLN (Limited Liability Company) on Prepaid consumers of Rayon Panam Pekanbaru City is considered to still have many shortcomings and is still not going well. In this study, the factors that influence the service of PT. PLN (Limited Liability Company) in the consumer prepaid Rayon Panam City of Pekanbaru, among others, investment study constraints, the lack of socialization of the National Electric Company to the Community, and lack of field officers.Keywords: Services, PT. PLN (Limited Liability Company), Prepaid Consumers